PERAN PERPUSTAKAAN DIGITAL DALAM MENCIPTAKAN RUANG PUBLIK (STUDI KASUS PERPUSTAKAAN DIGITAL UNIVERSITAS LAMPUNG) - Atin Istiarni; Endah Kurniasari (Program Studi Ilmu Perpustakaan, Fakultas Adab dan Ilmu Budaya, UIN Sunan Kalijaga Yogyaka, 2020)
The purpose of this study is to find out how the information age community understands digital public space and how the role of the University of Lampung's digital library in creating virtual public spaces. This research uses descriptive qualitative research methods. This research builds on the critical theory of public space proposed by Jurgen Habermas and Henry Lefebvre. Data collection through literature study and interviews. Data analysis includes three stages namely data reduction, data presentation, and conclusion or verification. Based on the results of the study, it was found that the public space in the information society is interpreted as a space where there is an infinite process of interaction. The role of the University of Lampung's digital library in creating public spaces includes (1) Providing freedom of access to systems and content, (2) giving freedom of expression to users through communication facilities between users and managers (3) Providing equality for anyone to access and utilize digital library applications The University of Lampung (4) has a legal umbrella in managing digital libraries (5) has a shared commitment to turn the University of Lampung's digital library into an ideal public space. Keywords: Digital Library, Public Spaces, Information Society.